A Prospective Randomized Non-Blinded Study of Safety and Efficacy of Bilastine Up-Dosing (40 mg) Versus Combination of Bilastine 20 mg With Levocetirizine 5 mg in the Treatment of Chronic Spontaneous Urticaria - Boggarapu Sneha; Murali Narasimhan; Priya Cinna T. Durai; Ramachandran Ramakrishnan (Wolters Kluwer Medknow Publications, 2024)
Introduction: Chronic spontaneous urticaria (CSU) is the most commonly diagnosed skin condition in dermatology outpatient departments. Second-generation antihistamines are shown to be effective in the control of CSU. As per the guidelines, a combination of antihistamines is less recommended due to the lack of synergistic effect, though used widely. Exploring effective treatment options are crucial, given the challenges posed by CSU. Aims and Objectives: To assess the safety and efficacy of Bilastine up-dosing versus combination of 20 mg Bilastine with 5 mg Levocetirizine in the treatment of CSU. Materials and Methods: This prospective randomized non-blinded comparative trial involved 62 patients, with 32 in group A and 30 in group B. Group A received Tablet Bilastine 20 mg bd, while Group B received a combination of Tablet Bilastine 20 mg and Tablet Levocetirizine 5 mg. Urticarial Activity Score 7 was performed at baseline and follow-up visits (every 2 weeks for 6 weeks). Results: Both groups had a higher number of male patients in the 20-30 years age group. Angioedema was present in 15.6% of group A and 23.3% in group B. After 6 weeks, both the groups showed a significant improvement in UAS 7 scores (P value <0.05). Group A demonstrated a remarkable reduction in UAS 7 from 19.4% to 0.03% with minimal side effects. Conclusion: Bilastine up-dosing proved to be efficient, secure, and well tolerated when compared to the combined dose of Levocetirizine 5 mg and Bilastine 20 mg, suggesting that up-dosing of Bilastine could be a valuable addition to the current medication arsenal with the minimal side effects.